2014
DOI: 10.1177/1933719113492206
|View full text |Cite
|
Sign up to set email alerts
|

Global Methylation in the Placenta and Umbilical Cord Blood From Pregnancies With Maternal Gestational Diabetes, Preeclampsia, and Obesity

Abstract: Emerging evidence indicates that maternal medical risk during pregnancy, such as gestational diabetes mellitus (GDM), preeclampsia, and obesity, predisposes the offspring to suboptimal development. However, the underlying biological/epigenetic mechanism in utero is still unknown. The current pilot study (N ¼ 50) compared the levels of global methylation in the placenta and umbilical cord blood among women with and without each risk condition (GDM, preeclampsia, and obesity) and explored whether the levels of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 35 publications
4
99
0
1
Order By: Relevance
“…Two studies that included only women 32 41 , found reduced global methylation with increasing BMI, however in one of these studies this only occurred in the presence of low concentrations of the methyl donor folate 32 . In contrast, two other studies that included both men and women from two different populations (Samoa and China) reported a positive relationship between global methylation in Peripheral Blood Leukocytes (PBL) and BMI 42 43 , and in a further study global methylation in placental tissues was higher in obese compared to lean women 40 . Only one study examined global histone methylation in obesity, showing substantially decreased levels of histone H3 lysine 4 dimethylation in adipocytes of overweight individuals compared with lean, with increased levels of lysine 4 trimethylation, observed in obese/diabetic individuals 9 .…”
Section: Global Methylation and Obesitymentioning
confidence: 56%
See 1 more Smart Citation
“…Two studies that included only women 32 41 , found reduced global methylation with increasing BMI, however in one of these studies this only occurred in the presence of low concentrations of the methyl donor folate 32 . In contrast, two other studies that included both men and women from two different populations (Samoa and China) reported a positive relationship between global methylation in Peripheral Blood Leukocytes (PBL) and BMI 42 43 , and in a further study global methylation in placental tissues was higher in obese compared to lean women 40 . Only one study examined global histone methylation in obesity, showing substantially decreased levels of histone H3 lysine 4 dimethylation in adipocytes of overweight individuals compared with lean, with increased levels of lysine 4 trimethylation, observed in obese/diabetic individuals 9 .…”
Section: Global Methylation and Obesitymentioning
confidence: 56%
“…All of the studies used BMI or changes in BMI to classify obesity, and two studies also used percentage body fat 32 33 . The majority of these investigations, including a large study combining four study populations, including up to 1254 individuals 34 , did not find an association between obesity and global methylation 33,[35][36][37][38][39][40] . Two studies that included only women 32 41 , found reduced global methylation with increasing BMI, however in one of these studies this only occurred in the presence of low concentrations of the methyl donor folate 32 .…”
Section: Global Methylation and Obesitymentioning
confidence: 99%
“…The differences were modest (−4.35% for GDM, N=8 versus 24 controls, and +2.46% for obesity, N=18 versus 32 controls) but as it is global methylation, which reflects CG-rich region methylation such as CpG islands or gene promoters, it can be considered as a substantial difference throughout the genome at large. This implies that maternal metabolism during pregnancy can impact whole-genome epigenetic marks (Nomura et al, 2014) but this does not allow comprehensive interpretation of the programming of adult diseases. With that goal, gene-specific methylation studies have been carried out.…”
Section: Reviewmentioning
confidence: 99%
“…Placenta DNA methylation at the global level was measured by the luminometric methylation assay (LUMA) in an American cohort of pregnancies complicated by GDM, pre-eclampsia or obesity (Nomura et al, 2014). This technique measures methylation of CG sites in the CCGG position at the global genome level.…”
Section: Gestational Diabetes Mellitus and Obesitymentioning
confidence: 99%
“…[50,51,[233][234][235] Physical inactivity correlates strongly with both childhood and adult obesity, and obese individuals are more likely to overindulge in western style energy dense foods. Already, we have described how parental obesity programs the offspring to develop NCCDs later in life through epigenetic modulatory changes that affect germ line and placental methylation levels, [167][168][169]175,236] and gut microbiota. [213] Increasing physical activity levels have also been shown to induce various epigenetic modifications beneficial to health (Table 2).…”
Section: Technological Advances and Physical Activity Levelsmentioning
confidence: 99%